2022
DOI: 10.1007/s40005-022-00563-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1α,25-dihydroxyvitamin D3 on the pharmacokinetics and biodistribution of ergothioneine, an endogenous organic cation/carnitine transporter 1 substrate, in rats

Abstract: Purpose This study aimed to investigate the effects of 1α,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) on the expression levels of organic cation/carnitine transporter 1 (OCTN1) as well as the pharmacokinetics and biodistribution of ergothioneine, an OCTN1 substrate, in rats. Methods Rats pretreated with 1,25(OH) 2 D 3 (2.56 nmol/kg/day) for four days were administered ergothioneine (2 mg/kg) intravenously. The expression levels of rat OCTN1 (rOCTN1) in organs were determined using real-time quantitative polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The animals were provided ad libitum access to both food and water in plastic cages under the specific conditions: a 12/12 h light/dark cycle, room temperature maintained at 20-25 °C, and relative humidity set at 40-60%. Before oral administration, the rats were fasted for 14 h. Pharmacokinetic studies were performed as reported previously (Yoon et al 2020;Vo et al 2022;Le et al 2023). Anesthesia was performed via intraperitoneal injection with Rompun ® (Bayer AG, Leverkusen, Germany) and Zoletil ® (Vibrac, Westlake, TX, USA).…”
Section: Application In Pharmacokinetics Studiesmentioning
confidence: 99%
“…The animals were provided ad libitum access to both food and water in plastic cages under the specific conditions: a 12/12 h light/dark cycle, room temperature maintained at 20-25 °C, and relative humidity set at 40-60%. Before oral administration, the rats were fasted for 14 h. Pharmacokinetic studies were performed as reported previously (Yoon et al 2020;Vo et al 2022;Le et al 2023). Anesthesia was performed via intraperitoneal injection with Rompun ® (Bayer AG, Leverkusen, Germany) and Zoletil ® (Vibrac, Westlake, TX, USA).…”
Section: Application In Pharmacokinetics Studiesmentioning
confidence: 99%
“…However, animals and humans are not known to synthesise ET, but instead accumulate it from dietary sources [21], especially mushrooms [22,23], via the action of a specific transporter, the organic cation transporter-novel, type 1 (OCTN1) [24], which after validation of its specificity is now widely named as the ET transporter (ETT) [25][26][27]. Studies in humans and other animals have shown that ET is avidly taken up and retained by the body [21,[27][28][29][30], which in addition to the existence of a selective transporter suggests that this compound may play important physiological roles.…”
mentioning
confidence: 99%